Interpretation of Hanīf in The Qur'an With a Late Antiquity and Near East Approach - Kusumo, Aditya Aryo Nur; Kusmana (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The word Hanīf in the Qur'an invites much academic debate regarding the meaning of the word. This word has many interpretations; if it refers to literature originating from recent Islam, it is interpreted as Islam. However, you get many alternative interpretations using interpretation through the Late Antiquity and Near East approaches. This paper aims to interpret the meaning of Hanīf using Late Antiquity and the Near East approach. This research shows that the meaning of Hanīf in the study of Islamic turrets has various meanings; there are at least five meanings in Tafsir At Tabari and Ibn Katsir. Furthermore, in the studies of Western scholars in analyzing the word Hanīf, it is studied based on the development of language in the Near Eastern context, which does not only mean Islam. In the social context, Hanīf means there is a monotheistic group that does not worship idols. Moneteism is defined as a submission to the One God and is not limited to one religion. The meaning of Hanīf here is more pluralistic and is not interpreted exclusively as meaning that Islam is the religion of the Prophet Muhammad. This means there are different interpretations of the word Hanīf using Late Antiquity and Near East approaches.